Family Relationships in an Aging Society - Terry Mills (EDIS)
For the elderly the family becomes more and more important as the need for support increases. Yet one must remember that the aging person and the family are all part of a larger society. Society impacts the resources and services available to older adults and their families. This document is FCS2210 FY625, one of a series of publications from the distance education in-service "Aging in the 21st Century." First published: September 2003.